“Identificación de Mildiu velloso (Peronospora corda) en el cultivo de arveja (Pisum sativum L.) en la comunidad de Monte Verde, cantón Montufar.” - Chirán Ayala, Wilson Gabriel (2019)
SUMMARY The present work of the research, the fact of being in order to identify the millennium incidence in the cultivation of life, the stage where it is most aggressive and the type of control more than more users of the community of Monte Verde cantón Montufar To achieve this, a bibliographic review was made on the pea crop, the characteristics of the product, the management conditions, the stages of cultivation, and the knowledge of the pests and diseases related to the product; Subsequently, several visits were made to the work area in order to identify the pea cultivators, and then apply the surveys. Within the surveys the following points are mainly evaluated, with respect to cultivation of the cultivation surface, soil analysis, fertilization, identification of the disease, symptoms, stage of greater aggressiveness of the disease, type of control and percentage of involvement in the production. Once the survey was carried out, the results were analyzed and the results were determined in the statistical tables, and then the conclusions and recommendations were drawn up. Keywords: Identify, diseases, surveys, downy mildew, vetch